Integrating agriculture, conservation and ecotourism : societal influences - Lopez Ortiz, Silvia; Campbell, W. Bruce (Issues in Agroecology - Present Status and Future Prospectus, 2012)
Issues In Agroecology approaches this complex panorama of interrelated topics by presenting authoritative, comprehensive, and analytical reviews by leading scientists in all areas of agroecology worldwide. Authors for each review are invited and represent a collaborative mix sufficient to provide strong summaries and scholarly advances that serve as foundations for discussion leading to novel routes of research activity, application of management methodologies, and education and outreach programs. Each review represents concise and up-to-date syntheses of the rapidly growing quantity of scientific information in each chosen topic within this highly interdisciplinary field. The authors for each review assess the present status of this knowledge as to whether or not it is effectively moving toward or contributing to increased sustainability. As a part of this assessment, the authors identify inadequacies, errors, and gaps in knowledge that may be hindering or opposing sustainability objectives. For each review, the authors ultimately discuss what might be needed to bring work and programs onto a better track towards achieving sustainability. Such informed assessments of the routes to realize future potential make the series an essential part of the scientific method and a necessity for researchers, teachers, students, and field professionals when dealing with increasing global environmental and socioeconomic change. This format will make Issues in Ecology a highly citable series that is guaranteed to enlighten research teams, technology users, educators, students, and the general public on the status and advances of agroecology around the world.